Pemanfaatan Fermentasi Kotoran Kambing dan Jerami sebagai Nutrisi Pakcoy (Brassica Rapa Chinensis) secara Hidroponik Deep Flow Technique di Kelurahan Banjar Sari Metro Lampung - Agus Mushodiq, Muhamad; Zainal Makmun, Muh Ngali (Bulletin of Community Engagement, 2024)
Since 2015, the conversion of agricultural land into residential and industrial land has been carried out massively by the people of North Metro, Lampung. Farming with conventional techniques has become ineffective because the nutrient elements in the soil have decreased significantly. Thus, the team carried out activities to make organic fertilizer from fermented goat manure and straw and held a production-scale DFT hydroponic system installation. The service method used is Asset Based Communities Development (ABCD). First, the results show that fermented goat manure in Pakcoy plants produces 15%-18% better yields than plants with AB Mix nutrition. On the side of the experimental experience in the field during the implementation of the service, the treatment of Goat Manure Fermentation and Straw and A-B mix produced the best plants with a total fresh weight yield of 30% compared to the A-B mix treatment alone or with goat manure fermentation alone. Second, there is a development in the welfare of the Banjarsari community in harvest sharing after collaborating in planting Pakcoy with students of the Ma'arif Nahdlatul Ulama Metro Islamic Boarding School. Third, the existence of hydroponic installations in the pesantren environment makes the relationship between the community and the students more transparent and creates a symbiotic relationship of mutualism between both parties. Keywords: Fermented Goat Manure, Hydroponic System, Asset Based Communities Development